Cuidado a mulheres usuárias de crack e outras drogas em situação de rua: aprendizagem experiencial e a prática das equipes de Consultório de Rua - Lídia Gonçalves Rabelo de Souza Almeida (2020)
This study aims at analyzing the professional qualification for dealing with drug user women under homeless condition. Specifically, it proposes the identification of strategies used in the qualification processes that generate experiential knowledge for professionals that attend homeless drug user women; the identification of content, subjects and references that have been used in the qualification process for professionals that treat homeless drug user women; and the identification of facilities and challengers throughout this formation process. A qualitative assessment was applied on this research. The experiential learning reference was adopted as a possibility to understand both initial and permanent qualification process of professionals who deal, unambiguously, the matters related to women in use of crack and other drugs. The participants were professionals from all the Street Clinics in Belo Horizonte, Minas Gerais, Brazil. Data was extracted from interviews and subsequently processed by means of the Critical Discourse Analysis proposed by Norman Fairclough. Results are organized into three categories: 1) Maternal condition: representation of homeless drug user women; 2) Street Clinic: care space of homeless drug user women; and 3) Qualification and experience: acquired knowledge.Homeless drug user women are functionally represented as pregnant women, as they are in the puerperium or because they have lost their children to the state, orphanages or to the extended family. The situation of orphan mothers stands out as a condition that draws attention from the perspective of professionals. There are different types of violence suffered by homeless women, from sexual, physical and institutional violence. The Street Clinic is an important care space that is effective through action on issues related to women's health and body with articulations with other services to ensure bonding, trust and support. In relation to learning, findings indicate that it comes from two dimensions: the formal education obtained in courses and training and the permanent education that takes place in daily work. The cycle of experiential learning takes shape with Reflective Observation that occurs when a professional observes a more experienced one and reflects on what he/she saw, transforming his/her learning and with the Concrete Experience that occurs when professionals feel and experience the practice in Street Clinics with the team and women, looking for concrete solutions to their problems. As conclusion, the formal training to deal with women drug users under street condition is still insufficient and it´s necessary to broad learning experiencial, such as training through academic leagues, internships and residency programs and permanent education.